1989
DOI: 10.1093/ajcn/50.3.675
|View full text |Cite
|
Sign up to set email alerts
|

Impact of iron supplementation on cognitive functions in preschool and school-aged children: the Indian experience

Abstract: Four studies examined impacts of iron supplementation on school children of various ages and both sexes. The first study investigated impact of iron-folic acid supplements for 60 d on cognition in 94 boys and girls aged 5-8 y. Improvement in total scores of the anemics was significantly higher than the nonanemics in 7-8-y-old children only. The second study assessed impacts of supplementation on cognition in 14 pairs of 5-6-y-old anemic boys, with clear beneficial effects on cognitive function. The third study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
149
0
7

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(173 citation statements)
references
References 5 publications
9
149
0
7
Order By: Relevance
“…The mean ± SD before and after treatment were 14.4 ± 13.4 and 10.5 ± 12.3, respectively. Previous studies in Indian children have also shown that children with iron deficiency anemia had lower levels of attention and concentration and that there was significant improvement with iron supplementation [28,29].…”
Section: Discussionmentioning
confidence: 92%
“…The mean ± SD before and after treatment were 14.4 ± 13.4 and 10.5 ± 12.3, respectively. Previous studies in Indian children have also shown that children with iron deficiency anemia had lower levels of attention and concentration and that there was significant improvement with iron supplementation [28,29].…”
Section: Discussionmentioning
confidence: 92%
“…Anemic children of more than 2 years also usually had poorer cognition and school achievements as compared to non-anemic once. They usually catch up in cognition with repeated testing and treatment but not in school achievement (33).…”
Section: Resultsmentioning
confidence: 99%
“…Iron deficiency has detrimental effects on physical and mental development of young children and is irreversible when iron therapy is started after the critical period for development has elapsed (Kretchmer et al, 1996). In older children and adolescents, iron deficiency, with or without anaemia, interferes with learning capacity and school achievement (Bruner et al, 1996;Seshadri & Gopaldas, 1989) as well as with growth (Chwang et al, 1988;Lawless et al, 1994) and appetite (Lawless et al, 1994). In pregnancy, anaemia can lead to reduced intrauterine growth and thus to low birth weight and peri-natal mortality (Scholl & Hediger, 1994).…”
Section: Introductionmentioning
confidence: 99%